Nekaj opazk o najsodobnejši beneški poeziji - Bandelj, David (Jezik in slovstvo, 2013)
A generation of poets operating in the regions of Benečija (Veneto), Rezija (Resia) and the Valleys of Kanal (Canale) and Ter (Torre) has produced a unique phenomenon in the Slovenian literature of the Italian region of Friuli Venezia Giulia. By examining the trends that distinguish these authors, I will attempt to exemplify their poetological decision to continue the tradition of vernacular poetry, which they upgrade with content selection that is fresh and modern, sometimes daring, in order to bring the level of vernacular poetry, traditionally perceived as folk poetry, to that of literary art.
Keywords: slovenska zamejska književnost; slovenska narečna poezija; Beneška Slovenija; Slavia Friulana